Patient Characteristics and Clinical Outcomes During the 2020–2021 COVID-19 Wave: An Observational Study at a Tertiary Hospital in Saudi Arabia - Ahmed, Omar B; Asghar, Atif; Bamaga, Majid; Abd El-Rahim, Ibrahim H; Mashat, Bassam; Khogeer, Asim; Assaggaf, Hamza (Curēus (Palo Alto, CA), 2024)
Background and objective The continued prevalence and threat of coronavirus disease 2019 (COVID-19) have been reported, and evidence suggests that several people still get infected with the virus. Gaining a thorough understanding of the patient demographic factors and laboratory findings could contribute to assessing the severity, mortality, and progression of COVID-19. In light of this, the current study aimed to evaluate the demographic characteristics, laboratory findings, and outcomes of confirmed COVID-19 patients at a tertiary hospital in the Kingdom of Saudi Arabia (KSA). Methodology We collected data spanning the period 2020-2021 from the electronic health records of Al-Noor Specialized Hospital, Ma including demographics (age, gender, and nationality), severity (i.e., ICU admission), length of hospital stay, mortality, and laboratory parameters. Results We observed an overall mortality rate of 10.2% (338 of 3,307 patients). The mortality rate was significantly higher in males (n=210; 62.1%) and patients aged more than 70 years (n=91; 26.9%). Patients with blood group O comprised 131 (29%) of the 338 non-survivors, followed by those with A (n=85; 25.1%) and B groups (n=79; 23.4%). The mortality rate among ICU patients was 63.3% (n=214). Furthermore, the following laboratory findings showed abnormal mean values in terms of severity and mortality in COVID-19 patients: hemoglobin (HB) concentration, white blood cell (WBC) count, lymphocyte count (LC), C-reactive protein (CRP), creatinine (CREA), and uric acid (UA) levels. Conclusions Old age, male gender, and certain laboratory findings have a critical role in the severity and mortality risk in COVID-19 patients. There was no significant association between blood type and the severity and mortality of COVID-19. Continuous monitoring based on these findings may be essential to managing COVID-19 patients.